Determinan Tax Avoidance pada Perusahaan Pertambangan dengan Good Corporate Governance sebagai Pemoderasi - Maria Delvina; Nadya Eka Putri; Vitryan Espa (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to empirically examine the effect of profitability, leverage, and firm size on tax avoidance practices, as well as the moderating role of Good corporate governance (GCG) in mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Method: This research employed a quantitative approach using secondary data obtained from annual reports and financial statements. The population consisted of mining companies listed on the Indonesia Stock Exchange, while the sample was selected using purposive sampling, resulting in 24 companies with 72 observations. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Finding: Leverage has a negative and significant effect on tax avoidance, while firm size has a positive and significant effect on tax avoidance. In contrast, profitability does not have a significant effect on tax avoidance. Furthermore, Good corporate governance moderates the relationship between leverage and firm size on tax avoidance, but does not moderate the relationship between profitability and tax avoidance. Novelty: The novelty of this study lies in its focus on mining sector companies during the post-pandemic period of 2022–2024 and the use of Good corporate governance, proxied by independent commissioners, as a moderating variable in examining tax avoidance practices